Frequency domain of renal autoregulation in the conscious dog - Wittmann, Uwe; Nafz, Benno; Ehmke, Heimo; Kirchheim, Hartmut; Persson, Pontus B. (American journal of physiology. Renal physiology, 1995)
The dynamic range in which renal blood flow (RBF) autoregulation occurs was determined in eight conscious foxhounds chronically catheterized in the abdominal aorta and implanted with a transit-time flow probe over the renal artery. Sinusoidal driving pressures (amplitude of 10 mmHg) were forced on the renal arterial pressure at different frequencies by a servo-control device, and transfer functions were calculated. Only one frequency range was found below which the gain of the transfer function declined and in which the phase angle increased (n = 8). This indicates the presence of a potent mechanism for renal autoregulation in the examined frequency range between 0.0031 and 0.08 Hz, which buffers changes in blood flow < 0.02 Hz. After furosemide treatment, one indicator for autoregulation (phase shift of transfer function) was significantly blunted at low frequencies (n = 6). Furosemide, however, did not reduce the phase shift to zero, suggesting that some autoregulation still remained in the frequency range between 0.04 and 0.08 Hz. In conclusion, autoregulation of RBF during sinusoidal changes in driving pressure between 0.0031 and 0.02 Hz is mediated by a single mechanism, which can be blocked by the acute administration of furosemide. The residual phase shift between arterial pressure and RBF in the transfer function observed during sinusoidal changes in driving pressure between 0.04 and 0.08 Hz suggests the presence of a second mechanism for RBF autoregulation.
Gesehen am 25.11.2024